Reduction in high rate of packet drop in reverse adhoc on-demand distance vector routing protocol under wormhole attack in mobile adhoc networks (2019)
Over the years the advent of wireless communication has made Mobile Ad-hoc Networks (MANETs) become more accessible platforms for easier exchange of data especially where it is expensive or impossible to establish fixed network infrastructure. These networks can offer a life-saving communication in a disaster or an emergency situation under well-equipped routing protocol as the quality of service provided by MANET is dependent on its routing protocol. This dependency has led to the development of several Multi-path routing protocol which guard against drop of unicast Route Reply packet associated with Ad-hoc On-Demand Distance Vector (AODV) - a single-path routing protocol. However, the performance of Reverse-AODV (a Multi-path routing protocol) can be vulnerable to high rate of packet drop under the influence of wormhole attack as the shortest path is selected and maintained for a given expiration time or until path fails. In this paper, we proposed an improved Reverse-AODV routing protocol (iR-AODV) which adopts different path routing; as a way of reducing the impact of wormhole attack on packets during transmission. The study simulated Reverse-AODV routing protocol and the improved version (iR-AODV) under wormhole attack. Both protocols were evaluated by considering different performance metrics under the same parameters such as number of nodes and simulation time. The results showed that the proposed iR-AODV recorded a smaller number of packet drop and higher Packet Delivery Ratio under wormhole attack when compared with R-AODV routing protocol.